The "Life" of st. Germogen, the arranger of Kirensk and Albazin monasteries. A unique document siberian hagiography of the mid-19th century - Vladimir Pushkarev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Hieromonk Hermogenes is one of the outstanding ascetics of the Russian Orthodox Church who carried out their ministry in Eastern Siberia. Two monasteries were founded here in the second half of the XVII century by his works. He was a good shepherd for the Russian first settlers of the Amur region, showing an example of Christian humility and piety. Immediately after the death of Hermogenes (1690), his popular veneration began, and in 1858 his life appeared.This is a handwritten text made up of two words spoken on the days of the memory of the righteous. In 1910, the manuscript was acquired by the Imperial Public Library. In this edition, for the first time, the full commented text of the Life is published. A preliminary analysis of this document made it possible to identify the sources used in its compilation and to establish the identity of the hagiographer. At the same time, a significant amount of historical facts contained in the text led to the preparation of a voluminous corpus of notes clarifying, supplementing or refuting this information. "The Life of St. Hermogenes" is a unique monument of Siberian hagiography of the middle of the XIX century. In addition to the obvious historical and cultural value, it is a convincing confirmation of the widespread popular veneration of Hermogenes in pre-revolutionary Russia and can serve as a good reason for his church glorification.